The effectiveness of scrapbook media on students' learning outcomes in thematic learning for 3rd grade at SDN Deket Kulon Lamongan - Fithriyah, Musa’adatul; Viyanti , Pratiwi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
Thematic learning is a teaching approach that combines or integrates various concepts from multiple subjects or fields of study into a single theme or specific topic. This research is motivated by the fact that there are issues with the implementation of Thematic Learning at SDN Deket Kulon Lamongan, including the insufficient use of thematic learning media by teachers, resulting in students' learning outcomes not fulfil the minimum completeness. Based on these problems, there is a need to employ learning media to aid students in understanding Thematic Learning concepts, thus enhancing their learning outcomes. The objective of this study is to employ the Scrapbook media and determine its effectiveness in Thematic Learning on the learning outcomes of 3rd Grade students at SDN Deket Kulon Lamongan. The research method used is quantitative research with an experimental design, specifically the one-group pre-test post-test design. The results of the research indicated that in the paired samples t-Test, the obtained significance value (sig) is 0.000 < 0.05, demonstrating the influence of Scrapbook media on students' learning outcomes in Thematic Learning for 3rd Grade at SDN Deket Kulon Lamongan. Furthermore, the average post-test scores of students showed an improvement of 16.9. Hence, it can be concluded that the Scrapbook media has a significant impact on enhancing students' learning outcomes in Thematic Learning for 3rd Grade at SDN Deket Kulon Lamongan.